The Conceptual Domain of Hunting and Its Negative Representation in Love: A Cognitive-Cultural Analysis - Raheleh Gandomkar; Masoomeh Hashemi (مطالعات زبان‌‌ها و گویش‌های غرب ایران)
As a cognitive process, metaphor objectifies mental concepts in such a tangible form that the study of human mental structure would be possible. The goal of this research is to study the conceptual domain of “hunting” and its negative representation in love “dating and marriage” based on the conceptual metaphor theory and cultural linguistics (Palmer, 1996; Sharifian, 2013). With a reference to the Persian corpus and Persian proverbs we studied the metaphor “marriage is hunting” and its negative representation. Three micro metaphors obtained were “marriage is hunting,” “marriage is theft,” and “marriage is captivity,” which through linguistic metaphoric expressions such as hunting, snapping, enthralling, grabbing, snatching, ensnaring, catching, trapping, capturing, enslaving, and harnessing all bearing a negative emotional connation both in the case of man or the woman. The research findings showed that we witness a negative metaphorical representation of hunting in “marriage”. Sometimes a woman is a valuable catch and the prey for a male hunter but she sometimes takes the role of a hunter and the man is the prey. The results showed that factors such as gender, commitment to cohabitation and the suitability of couples in terms of appearance, economy, age, celibacy and ethical orientation affect metaphorical representations. Introduction Metaphor is a cognitive process that represents abstract concepts in tangible form, enabling the study of human mental structures. Recently, there has been growing interest among scholars in exploring the ideological dimensions of metaphor. Gender and ideology are particularly relevant when examining conceptual areas like love and marriage. Cognitive linguistics has extensively studied the target domains of love and marriage, identifying numerous source domains used to conceptualize them. However, the source domain of hunting still requires further exploration from a gender perspective. This study aims to examine the conceptual metaphors of love, seduction, and hunting, focusing on gender and culture. Our research findings reveal a negative metaphorical representation of hunting in the context of dating and marriage. Sometimes, women are portrayed as valuable prey for male hunters, while in other instances, the roles are reversed. In this article, we address the following questions: 1) What are the micro-metaphors of the macro-metaphor "marriage is hunting" in the domain of love? 2) Which micro-metaphor has the highest frequency, and what accounts for its prevalence? 3) What factors contribute to the negative metaphorical representation of the macro-metaphor "marriage is hunting" in the context of dating and marriage? Our research is grounded in conceptual metaphor theory and cultural linguistics (Palmer, 1996; Sharifian, 2013) and relies on the Persian corpus and Persian proverbs to study the metaphor "marriage is hunting" and its negative representation. Methodology and Theoretical Framework This descriptive-analytical study utilizes a corpus of Persian language data extracted from 30 contemporary Persian works. To identify the conceptual metaphor "marriage is hunting," the following methods have been employed: